Cyclic oversupply of residential development-instant fragmentation of traditional mono-centric city - Roose, Antti (2014)
This study examines the residential expansion of Tartu urban region in Estonia. This paper assesses the evolution of planning practices to get a comprehensive understanding of the driving forces behind the dynamics of residential development in the conditions of suburbanisation at the emerging market. The study focuses explicitly on speed and scope of planning cycles by matching the operational scale of physical planning with master plans, parcels as survey elements and real estate transactions. The results show that housing bubble for residential markets, following recession in the 2000s and recovery in 2010s, their manifestation in the local planning practices and housing development scene call for a more strategic thinking of how we understand and evaluate spatial changes. A profit-driven supply-side entrepreneurial intervention to planning during the growth years put too much emphasis on delivery of quantity, namely land supply, rather than the benefits of quality, allocation choices and social dimension, often overriding regulative frameworks. Discretional ad hoc solutions and fragmented site-by-site development have been the main approaches in issuing land use change with little implication of housing demand. Extensive master planning for residential development has resulted in massive ‘overbooking’ of urban land parcels as only quarter of planned urban core and half of the planned periurban development has been carried out.